2022
DOI: 10.1002/jcb.30235
|View full text |Cite
|
Sign up to set email alerts
|

KLF8 is activated by TGF‐β1 via Smad2 and contributes to ovarian cancer progression

Abstract: Krüppel-like factor 8 (KLF8) is a transcription factor expressed abnormally in various cancer types and promotes oncogenic transformation. However, the role of KLF8 in ovarian cancer (OC) progression remains unclear. This study reports that transforming growth factor-β1 (TGF-β1)/Smad2/KLF8 axis regulates epithelial-mesenchymal transition (EMT) and contributes to OC progression. We analyzed the KLF8 expression in OC cells and tissues, wherein a significant overexpression of KLF8 was observed. Increased KLF8 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The TGF-b1 signaling pathway involves binding of mainly TGF-b1 ligands to their receptors, and the phosphorylated TGF-b1 receptor can activate various signaling pathways, including the Smad2/3, Ras and PI3K pathways [ 38 ]. Several studies have shown that TGF-b1 signaling can be associated with the cause and development of cancer by regulating cell migration, the tumor microenvironment and metastatic capacity [ 39 43 ]. In ovarian cancer, TGF-b1 has been shown to regulate proliferation, the EMT, the stem cell phenotype, and metastasis [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-b1 signaling pathway involves binding of mainly TGF-b1 ligands to their receptors, and the phosphorylated TGF-b1 receptor can activate various signaling pathways, including the Smad2/3, Ras and PI3K pathways [ 38 ]. Several studies have shown that TGF-b1 signaling can be associated with the cause and development of cancer by regulating cell migration, the tumor microenvironment and metastatic capacity [ 39 43 ]. In ovarian cancer, TGF-b1 has been shown to regulate proliferation, the EMT, the stem cell phenotype, and metastasis [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…KLF expression is often altered in tumors, and this is essential for tumor development. For instance, KLF8 is activated by transforming growth factor-β1 (TGF-β1) via SMAD2 and contributes to ovarian cancer progression [65,66]. Cherukunnath et al reported that the TGF-β1/SMAD2/KLF8 axis regulates epithelial-mesenchymal transition and contributes to ovarian cancer progression [66].…”
Section: Discussionmentioning
confidence: 99%
“…KLF8 regulates the transcription of genes involved in diverse biological processes, such as proliferation, inflammation, migration and invasion 43 . KLF8 is widely expressed in various tissues, and abnormal expression of KLF8 is manifested in several cancers, including lung, gastric and ovarian cancers 44,45 . Previous studies have reported that KLF8 plays important roles in DNA repair and apoptosis resistance 43 .…”
Section: Discussionmentioning
confidence: 99%
“… 43 KLF8 is widely expressed in various tissues, and abnormal expression of KLF8 is manifested in several cancers, including lung, gastric and ovarian cancers. 44 , 45 Previous studies have reported that KLF8 plays important roles in DNA repair and apoptosis resistance. 43 In our study, we found that KLF8 is a downstream target of miR‐1252 and that miR‐1252 is responsible for circ‐ILF2 induced KLF8 upregulation.…”
Section: Discussionmentioning
confidence: 99%